Behind eco-innovation: Managerial environmental awareness and external resource acquisition. (15th December 2016) - Peng, Xuerong; Liu, Yang
Abstract: What drives eco-innovation? This study integrates the managerial cognition perspective and the resource dependency perspective to examine how managerial environmental awareness (i.e., managerial environmental risk awareness and managerial environmental cost-benefit awareness) and external resource acquisition (i.e., from business networks and political networks) affect corporate eco-innovation activities (i.e., eco-management innovation, eco-process innovation, and eco-product innovation), and analyzes their interaction effects. A sample of 144 firms in Zhejiang province in China supports our hypotheses. Highlights: The impacts of managerial environmental awareness on eco-innovation are examined. The impacts of managerial environmental risk and cost-benefit awareness are examined separately. The impacts of external resource acquisition on eco-innovation are examined. The impacts of business and government resource acquisition are examined separately. The interplay of managerial environmental awareness and external resource acquisition are examined.